Fright, attention, and joy while killing zombies in Virtual Reality: A psychophysiological analysis of VR user experience. Issue 6 (7th January 2021) - Bender, Stuart M.; Sung, Billy
Abstract: To date, research on the user experience of Virtual Reality (VR) games is sparse even though VR and immersive gaming experiences are emerging as a substantial consumer based within the videogame industry. Using facial electromyography and skin conductance response measurement, the current research presents the first psychophysiological evidence to show that: (1) VR games may heighten affective responses such as fear and arousal; (2) different levels of immersion in various gameplay modes may evoke higher affective responses; and (3) these heightened affective responses significantly correlate with users' experience of enjoyment at the precise onset of the affective response. Due to the second‐by‐second nature of psychophysiological measurement, the study's findings also pinpoint a specific sequence (i.e., entrapment in a dark room) within the gameplay that significantly evoked nearly 2.5‐times higher fear with arousal as well as enjoyment. These findings contribute to the ongoing study of VR in the fields of media psychology, media studies, human‐computer interaction studies, and marketing by demonstrating the strong link between immersion, affective responses, and positive user experience toward a horror VR game and their marketing implications.